Efektivitas Program Sistem Informasi Kesejahteraan Elektronik (E-SIK) di Dinas Sosial Kota Surakarta - Alfia Nur Annisa; Is Hadri Utomo (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
E-SIK is the implementation of e-government in Surakarta City as a solution to problems in data collection for the poor. The purpose of this study was to analyze the effectiveness of the E-SIK application program in relation to data collection of the poor in Surakarta. The theory used is Campbell's Effectiveness Theory (in Richard M, 2005) which has the following aspects: a) Program success, b) Target success, c) Satisfaction with the program, d) Input and output levels, e) Achievement of overall goals. The research method used is descriptive qualitative research method with data collection techniques through interviews, and documentation. The sampling technique used purposive sampling technique. Furthermore, the analytical technique used is the research analysis technique of Miles and Huberman. The output of this research is in the form of a research thesis on the effectiveness of the Electronic Welfare Information System (E-SIK) in Surakarta City. The results show that the effectiveness of the E-SIK Program has been running quite well, from the 5 aspects studied, 3 of them have been running effectively, namely aspects of program success, aspects of input and output levels, and aspects of overall goal achievement. For the other 2 aspects, namely the aspect of target success, it has been running quite well but in its implementation there are still various problems so that it is not optimal, then for the aspect of program satisfaction it is still not effective.